2017
DOI: 10.1186/s10194-017-0800-8
|View full text |Cite
|
Sign up to set email alerts
|

The KATP channel in migraine pathophysiology: a novel therapeutic target for migraine

Abstract: BackgroundTo review the distribution and function of KATP channels, describe the use of KATP channels openers in clinical trials and make the case that these channels may play a role in headache and migraine.DiscussionKATP channels are widely present in the trigeminovascular system and play an important role in the regulation of tone in cerebral and meningeal arteries. Clinical trials using synthetic KATP channel openers report headache as a prevalent-side effect in non-migraine sufferers, indicating that KATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 98 publications
(99 reference statements)
0
43
0
Order By: Relevance
“…Nevertheless, the possibility of the involvement of other potential channel targets besides A-type channels in the pathophysiology of migraine can not be ruled out. Although further investigation is clearly necessary in rats with ES-induced migraine, emerging evidence suggests that K ATP channels may play a pivotal role in migraine pathogenesis and could be a potential novel therapeutic anti-migraine target [60].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the possibility of the involvement of other potential channel targets besides A-type channels in the pathophysiology of migraine can not be ruled out. Although further investigation is clearly necessary in rats with ES-induced migraine, emerging evidence suggests that K ATP channels may play a pivotal role in migraine pathogenesis and could be a potential novel therapeutic anti-migraine target [60].…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies of these mutations have shown that they can result in defective regulation of glutamatergic neurotransmission and the excitatory/inhibitory balance in the brain, which lowers the threshold for cortical spreading depression, a wave of cortical depolarization thought to be involved in headache initiation mechanisms (Sutherland and Griffiths, 2017). KATP channels are also connected to several key molecules in migraine pathogenesis, particularly nitric oxide, CGRP, PACAP and PGI2 known to provoke migraine attacks (Al-Karagholi et al, 2017). Human experimental models have demonstrated that the activation of the cAMP and cGMP pathways can trigger headache in healthy volunteers and migraine attacks in migraine sufferers (Ashina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, neurovascular signaling mechanisms involving the dural vasculature may contribute to the complex pathobiology of migraine, as well as cluster headache. 4,15,16 Vascular smooth muscle potassium channels play a crucial role in the regulation of arterial diameter. Activation of these channels results in membrane potential hyperpolarization promoting a decrease in the activity of voltage-dependent calcium channels (VDCCs) that ultimately leads to decreased intracellular calcium concentration ([Ca 2þ ] i ), smooth muscle relaxation, and vasodilation.…”
Section: Introductionmentioning
confidence: 99%